Penerapan Algoritma C4.5 Untuk Klasifikasi Penempatan Tenaga Marketing - Eka Fitriani; Riska Aryanti; Atang Saepudin; Dian Ardiansyah (Paradigma, 2020)
Marketing is a job that has a scope of work to market a product. Marketing is at the forefront of the company. The problem that often occurs in companies is not having a reliable marketing force. The problem arises because the process of accepting new marketing is still not done professionally. This happens because there is no systematic standard method to assess the feasibility of marketing candidates. Therefore it is necessary to analyze the marketing placement so that it can determine the feasibility of a new marketing placement problem. Through the results of the analysis of new marketing placements, it can be seen whether the marketing candidates passed or did not qualify. Of the problems that exist testing the data mining classification method to find out the algorithm to predict marketing feasibility is to use an algorithm that is C4.5. After testing with the C4.5 algorithm the results obtained are that the C4.5 algorithm produces an accuracy value of 91.10% and an AUC value of 0.921 with a diagnosis level of Excellent Classification. So that the conclusion C4.5 algorithm is a good algorithm to be applied to the feasibility of marketing placement. Keywords : Marketing Feasibility, Data Mining, C4.5